Economic Integration, Institutional Differences and Regional growth - Carlie Geerdink (European Regional Science Association (ERSA), 2013)
Despite the process of economic integration, recently we have been witnessing divergence of regions in their economic performance and development, resulting in considerable differences income, employment and welfare. This is neither socially nor politically desirable. Markets, like the labour market, which are relatively rigid, are seen as an obstacle for economic convergence. We suspect that divergence is also caused by other factors. All kind of intangibles, such as the legal structure, the public administration can lead to comparative dis- / advantages. These intangibles are part of the institutional setting of a region and have public good characteristics. In this paper we analyse the effects of differences in institutional setting in the process of economic integration. The paper is organized as follows. First, in section 2, we introduce the model we use to analyse the integration process.. We use an OLG model with a log?linear utility and production function. The production function is a neo-classical production function with public capital, private capital and labour, characterized by diminishing returns to scale for public, private capital and labour. Public capital exhibits positive externalities. Both public and private capital is fully depreciated during its period of use. In section 3 we look at the economic development of the regions separately, the autarchy case. Different institutional settings, results in difference productivity and different economic development of the regions. In section 4 we introduce economic integration, and assume mobility of private capital, labour, but immobility of public capital. Labour commutes; if the wage rate in the other region is higher, but workers will spend their income in their resident region. In section 5 the effects of integration are analysed. Integration increases overall efficiency and the overall economic development of the two regions. However capital moves from the less productive region to the more productive one, resulting from a difference in return on private capital. As a result, return on private capital decreases for the more productive region together with return on public capital, but output increases. For the less productive region the reverse happens: return on private and public capital increases but output decreases. This arbitrage process continues until the private returns on capital between the two regions equalize. Integration leads to divergence in the economic development of the two regions compared with the autarchy situation. There is no incentive for the losing region to co-operate.
Keywords: R11; R13; O47; 330